You have new items in your feed. Click to view.
Q: (3x – 1)(2x + 5)
A: This conversation has been flagged as incorrect. New answers have been added below ....
Original conversation
User: (3x – 1)(2x + 5)

Weegy: 5x.
aaaaaaaaaaaaaaa|Points 3996|

User: (5x – 3y)2

Weegy: 31/8 and 25/8
yestfl|Points 1444|

User: Perform the indicated operations and simplify. 5x – 4x[8 – 3(x – 2)]

User: Factor completely relative to the integers. 49a2b – b3

Question
Updated 7/1/2014 11:45:46 PM
This conversation has been flagged as incorrect.
Flagged by alfred123 [7/1/2014 3:19:20 PM], Followed by yeswey, Unfollowed by yeswey
Rating
3
(3x - 1)(2x + 5)

= 6x^2 + 15x - 2x - 5;

= 6x^2 + 13x - 5

Confirmed by yumdrea [7/1/2014 3:27:14 PM]
3
(5x - 3y)^2

= (5x - 3y) (5x - 3y)

= 25x^2 - 15xy - 15xy + 9y^2

= 25x^2 - 30xy + 9y^2
Confirmed by yumdrea [7/1/2014 3:27:41 PM]
3
5x – 4x[8 – 3(x – 2)]
= 5x - 4x[8 - 3x + 6]
= 5x - 4x(14 - 3x)
= 5x - 56x + 12x^2
= 12x^2 - 51x

Confirmed by jeifunk [7/1/2014 7:34:55 PM], Unconfirmed by jeifunk [7/1/2014 7:35:28 PM], Confirmed by jeifunk [7/1/2014 7:36:10 PM], Unconfirmed by jeifunk [7/1/2014 7:53:48 PM], Confirmed by jeifunk [7/1/2014 7:53:50 PM]
3
49a^2b – b^3
= b(49a^2 - b^2)
= b(7a + b)(7a - b)
Confirmed by jeifunk [7/1/2014 7:54:42 PM]
@Alfred,
All are correct except for the last but one line. It should be "12x^2" other than "-12x^2". I think thats a typo since the last step is correct.
yeswey, as discussed before with a clarification from Weegy Admin , please do not flag an answer that has a clear typo on solutions. Alfred has the correct final answer, so it was clearly a typo. Instead of flagging and adding a new answer, please notify the expert on his/her feed to fix the typo.
Hi Andrew & all,

Obviously, the answer is correct, just took x as b. Shouldnt this be considered typo? Or this is an intended incident?
The answer is correct but Alfred's solution is wrong.
5x -(-12x2+56x) = 5x - 56x + 12x^2
Yes, I believe it was a typo. I unflagged it.
jeifunk, it was pretty basically just the same as yeswey's solution, it's just that Alfred put 5x - 56x - 12x^2 instead of 5x - 56x + 12x^2 since he was able to get the correct answer.

Yeswey, you have flagged my answers for typo and I don't mind since it is a math question, we should be more careful in putting symbols as it will make the solution confusing and inaccurate.

We should always check our answers for missing symbols after we hit add answer. So we can always correct it.

jeifunk,
I really dont mind it, either. I beleive incorrect answers MUST BE CORRECTED. Otherwise later incoming auto answers for the same question will still remain incorrect. But i think rules should be the same to all of us, and it seems that you guys (moderators) hold several different opinions on some issues, just a little bit though.
yeah but if the solution is 5x - 56x - 12x^2, the answer should be -12x^2-51x, its just confusing.

yeswey, I am just confused on the links you were sending, but I'm pretty sure that we are not supposed to flag answers that has clear typos, we are also not supposed to add a new answer. That's because we still don't have EDIT buttons on the archive to fix any typos.
The thing is, you have already flagged the answer and add a new one before the expert could even fix his/her typos. You should post a link to the expert's feed and let him/her know.

I also forgot to tell you to delete your own typo and add a new one, but don't duplicate answers. That's all.
Sorry for the typo. I'll just delete it. I won't add the correct one since yeswey has done it for me. I'd be careful next time when answering a math question. Maybe I was just sleepy that time and made a mistake with the sign. Thanks.
@andrew,
Thank you.
The internet connection speed is very slow.
Questions asked by the same visitor
Solve: |x - 4| = 2
Weegy: + User: Solve. Write the solution in interval notation. |x + 4| 6 User: Write as an absolute value inequality. x is more than 7 units from 3 User: Solve: |2x – 7| = 3 A. 5, 2 B. 5, –2 C. –5, 2 D. –5, –2 Weegy: x = -5 User: Solve: |x + 3| = 2x + 1 A. 2 B. -4/3 C. 2, -4/3 D. 2, 4/3 Weegy: x = -5 User: Solve: |x + 3| = 2x + 1 Weegy: x = -5 User: One computer printer can print a company's mailing labels in 40 minutes. A second printer would take 60 minutes to print the labels. How long would it take the two printers, operating together, to print the labels? User: A musician is planning to market a CD. The fixed costs are \$330 and the variable costs are \$5 per CD. The wholesale price of the CD will be \$8. For the artist to make a profit, revenues must be greater than costs. How many CDs, x, must be sold for the musician to make a profit? (More)
Question
Updated 7/23/2014 12:09:54 PM
Question on: One computer printer can print a company's mailing labels in 40 minutes. A second printer would take 60 minutes to print the labels. How long would it take the two printers, operating together, to print the labels?

It will take 24 minutes to the two printers, operating together, to print the labels.

Solution:

Let x= time it takes both computers working together
Then both computers print at the rate of 1/x mailing labels per min
First computer prints at the rate of 1/40 mailing labels per min
Second computer prints at the rate of 1/60 mailing labels per min
So:
1/40 + 1/60 = 1/x multiply each term by 120x
3x+2x=120
5x=120
x=24 min- - - - -time required when both computers work together
CK
In 24 min first computer completes (1/40)*24=24/40 of the mailing labels

|x - 4| = 2;
x - 4 = 2; x = 2 + 4; x = 6
-(x - 4) = 2; -x + 4 = 2; -x = 2 - 4; -x = -2; x = 2

x = 6 or x = 2
|2x – 7| = 3;
2x - 7 = 3; 2x = 3 + 7; 2x = 10; x = 10/2; x = 5;
-(2x – 7) = 3; -2x + 7 = 3; -2x = 3 - 7; -2x = -4; x = -4/-2; x = 2

x = 5 or x = 2
Is the algebraic expression a polynomial? If so, give its degree. 9x3 + 6x6 + 8
Question
Updated 6/28/2014 2:59:45 PM
9x^3 + 6x^6 + 8 is a polynomial with a degree of 6.
9x + 8 = 2x + 8
Weegy: 9x + 8 = 2x + 8, 9x - 2x = 8 - 8 7x = 0 x = 0/7 x = 0 (More)
Question
Updated 6/16/2014 2:11:11 PM
Multiply and simplify. (3x – 1)(2x + 5) A. 6x2 – 13x – 5 B. 6x2 – 17x – 5 C. 6x2 + 13x – 5 D. 6x2 + 17x – 5
Question
Updated 6/16/2014 2:10:48 PM
(3x – 1)(2x + 5)

= 6x^2 + 15x - 2x - 5

= 6x^2 + 13x - 5
Multiply and simplify: (3x2 – 2x – 1)(x2 + x + 5) A. 3x4 + 2x3 + 12x2 – 11x – 5 B. 3x4 + x3 + 12x2 – 10x – 5 C. 3x4 + x3 + 12x2 – 11x – 5 D. 3x4 + x3 + 14x2 – 11x – 5
Question
Updated 7/13/2014 1:57:28 PM
(3x^2 – 2x – 1)(x^2 + x + 5)
= 3x^4 - 2x^3 + 3x^3 - x^2 - 2x^2 + 15x^2 - x - 10x - 5
= 3x^4 + x^3 + 12x^2 - 11x - 5
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 254 [Total 272] Ratings 0 Comments 184 Invitations 7 Offline
S
L
R
Points 135 [Total 286] Ratings 1 Comments 5 Invitations 12 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.